BLACK HIP-A CASE OF OCHRONOTIC ARTHROPATHY - Mathias, Lawrence J.; Mathias, Michelle; Shetty, Padma; Rai, Ravindranath (Journal of Health and Allied Sciences NU, 2011)
alkaptonuria an autosomal recessive disorder in which a deficiency of homogentessic acid oxidase results in the accumulation of homogentessic acid which is deposited in connective tissues notably in the intervertebal disc,articular cartilage and tendons leading to their early degeneration.Here we describe a case of ochronotic arthropathy
Keywords: Alkaptonuria; Ochronotic arthropathy